Predictors of personal best performance in the hammer throw for U.S. collegiate throwers - Judge, L. W.; Bellar, D.; McAtee, G.; Judge, M. (International Journal of Performance Analysis in Sport, 2010)
The purpose of this study was to investigate the variables that contributed most to maximum throwing distance in the hammer throw event in track and field. A 41-item survey instrument was developed to collect data regarding national level collegiate hammer throwers throughout the United States. Multiple regression analysis for hammer throw personal record (PR) yielded a significant model (r=0.811, p=0.001) with the following predictors: number of throws per year, number of years throwing the hammer, NCAA division, back squat, and type of hammer technique. The model explained in excess of 65% of the variance in hammer technique among the respondents (r2=0.658). These results provide quantitative information for coaches and athletes involved in the hammer throw event about the importance of years of experience, volume of training and strength levels. Furthermore, the results may provide some insight into the obstacles and barriers limiting the development of US hammer throwers.